THE STUDY ON NETWORK INFORMATION SECURITY - Muminov Sanjar Saidkulovich; Shoraimov Husanboy Uktamboyevich; Qudratov Shukrullo Abdiqunduz o’g’li (Galaxy International Interdisciplinary Research Journal, 2021)
The connectivity and openness of computer network greatly facilitates the sharing of resources. However, accompanied with the growing popularity and the expansion fields of network usage, unauthorized access, network data theft, hacker attacks, virus attacks and a series of network information security problems become visible. This paper focuses on the need of legislation protecting network information security, the existing regulations as well as the design principles of network information security system, and further explores the precautions on network information security.